Seismic-Resilient Light Steel Frame Structural Model with Genetic Algorithm Optimization - Rendy Perdana Khidmat; Beta Paramita; Rahmat Kurniawan; Kirtinanda Kirtinanda; Kustiani Kustiani; Nova Asriana (Jurnal Arsitektur, 2026)
This research aims to minimize the impact of damage caused by earthquakes on simple residential houses, as well as to propose a preliminary draft of a model for light gauge steel frame (LGSF) construction by designing a light gauge steel frame structure (LGSF) modules with a new configuration using a genetic algorithm approach in the grid and profile design process. Rhinoceros + Grasshopper and Karamba plugins are used to simulate structural performance while octopus is used to run multi-Objective Optimization. From the Octopus iterations, a total of 319,614 designs were generated through genetic iterations, with the top 10 designs based on structural performance selected through fitness function evaluation. The displacement was reduced by 29.77 cm (14.39%) compared to the baseline model. However, the length was shown to increase by 18 cm (6.8%). This research contributes to the design method and optimization of the overall use of LGSF.